Comorbidities and causes of death in the management of localized T1a kidney cancer. (16th June 2014) - Patel, Hiten D; Kates, Max; Pierorazio, Phillip M; Gorin, Michael A; Jayram, Gautam; Ball, Mark W; Hyams, Elias S; Allaf, Mohamad Ezzeddine
Abstract : Objective: The objectives of the present study were analyze specific comorbidities associated with survival and actual causes of death for patients with small renal masses, and to suggest a simplified measure associated with decreased overall survival specific to this population. Methods: The Surveillance, Epidemiology and End Results‐Medicare database (1995–2007) was queried to identify patients with localized T1a kidney cancer undergoing partial nephrectomy, radical nephrectomy or deferring therapy. We explored independent associations of specific comorbidities with causes of death, and developed a simplified cardiovascular index. Cox proportional hazards, and Fine and Gray competing risks regression were used. Results: Of 7177 Medicare beneficiaries in the study population, 754 (10.5%) deferred therapy, 1849 (25.8%) underwent partial nephrectomy and 4574 (63.7%) underwent radical nephrectomy with none of the selected comorbidities identified in 3682 (51.3%) patients. Congestive heart failure, chronic kidney disease, peripheral vascular disease, chronic obstructive pulmonary disease, diabetes and cerebrovascular disease were associated with decreased overall survival. The cardiovascular index provided good survival risk stratification, and reclassified 1427 (41%) patients with a score ≥1 on the Charlson Comorbidity Index to a 0 on the cardiovascular index with minimal concession of 5‐year survival. Conclusions: Congestive heart failure, chronic kidney disease, peripheral vascular disease, chronic obstructive pulmonary disease, diabetes and cerebrovascular disease were associated with decreased overall survival among Medicare beneficiaries with small renal masses. The cardiovascular index could serve as a clinically useful prognostic aid when advising older patients that are borderline candidates for surgery or active surveillance.